1999
DOI: 10.1021/es9811142
|View full text |Cite
|
Sign up to set email alerts
|

Extractable Organohalogens (EOX) in Sediment and Biota Collected at an Estuarine Marsh near a Former Chloralkali Facility

Abstract: Extractable, organically bound chlorine (EOCl), which is determined by neutron activation analysis (NAA), has been used as a measure of pollution by chlorinated organics. In this study, the concentrations and distribution of extractable organohalogens (EOX = EOCl + EOBr + EOI) were measured in sediment, blue crab, fishes, birds, and terrapin collected at an estuarine marsh and a nearby creek contaminated by the disposal of wastes from a former chlor-alkali facility. The concentrations of the organohalogens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Since clapper rails for this study were also used in a human health risk study for those who may consume these birds, PCBs were not adjusted for lipid content. However, clapper rails collected from our study area have been documented to have a wet weight fat content of 2.5% for muscle and 4.1% for liver (Kannan et al 1999).…”
Section: Home Rangementioning
confidence: 86%
See 1 more Smart Citation
“…Since clapper rails for this study were also used in a human health risk study for those who may consume these birds, PCBs were not adjusted for lipid content. However, clapper rails collected from our study area have been documented to have a wet weight fat content of 2.5% for muscle and 4.1% for liver (Kannan et al 1999).…”
Section: Home Rangementioning
confidence: 86%
“…Laboratory studies on fish (Fundulus heteroclitus) from the estuary have suggested that both contaminants have direct and transgenerational effects (Baker Matta et al 2001). Numerous studies have described the distribution and characterization of both Hg and Aroclor 1268 in sediments and soil from this system, as well as report contaminant concentrations from biota opportunistically collected from the estuary (Kannan et al 1997(Kannan et al , 1998a(Kannan et al , 1999Maruya and Lee 1998). However, no study to date has characterized the contaminant burden of a population residing at known spatial locations within LCP and the contaminant loads of their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…This is also evident when previous studies documenting the congener profiles and total contaminant loads of Aroclor 1268 in sediments and the biota from this estuary are compared (Kannan et al 1997(Kannan et al , 1998(Kannan et al , 1999Cumbee et al 2008). Moreover, given that the purpose of this study is to use the Aroclor 1268 congener mixture as a marker, any temporal diminishment of this PCB mixture due to weathering or natural attenuation does not confound the study.…”
Section: Introductionmentioning
confidence: 76%
“…Previous studies from LCP have indicated that this is the only Aroclor mixture found in elevated levels (Kannan et al 1997(Kannan et al , 1998(Kannan et al , 1999Cumbee et al 2008). Therefore, hereafter, these primary congeners of the Aroclor 1268 mixture will be collectively referred to as the Aroclor 1268 mixture.…”
Section: Sample Preparation and Analysismentioning
confidence: 99%
“…These substances are often present in relatively high concentrations in sediments, which facilitates their chemical analysis. Bottom sediments are therefore widely used in aquatic environments as indicators for assessing the levels and distribution pattern of organochlorine compounds discharged from pulp mills (Svanberg and Bengtsson 1996), as well as from chloralkali facilities (Kannan et al 1999).…”
Section: Introductionmentioning
confidence: 99%